تضمين مناهج التربية الاسلامية لمفهوم السِّلْم من وجهة نظر المعلمين: المدارس العربية بكوالا لمبور نموذجا: INCLUSION THE CONCEPT OF PEACE IN ISLAMIC EDUCATION CURRICULUM FROM TEACHERS’ PERSPECTIVE: ARAB SCHOOLS IN KUALA LUMPUR AS A MODEL - Haiyan Daud, Aminah Li; Ismail, Wail Muin; Zailani, Muhammad Azhar (Journal of Islamic Educational Research, 2021)
The view of the Islamic education curriculum on the function of peace and its roles does not change with the change of the requirements of modern life. It is the basis of all civilization and progress. Islamic education begins with an attempt to implement peace first in the conscience of the human individual so that his heart is reassured. Then in the family environment because it is an essential cell in building a safe society. Then in the midst of the society to which that human individual belongs. It is surrounded by nations and peoples for acquaintance, diversity and solidarity in the spirit of human tolerance. This study aims to collect the purposes of peace from the Noble Qur’an and the Sunnah, And then to identify the level of inclusion of these meanings in the curricula of Islamic education in Arab schools in Kuala Lumpur. The meanings of peace have been divided into three axes; peace of the individual; peace in the family; The third axis includes peace in society. Whereas, a questionnaire designed to measure this was distributed to (119) teachers of the Islamic education curriculum in Arab schools in Kuala Lumpur. The results showed the low level of inclusion in Islamic education curricula of the foundations of peace, and that it does not amount to achieving the five religious necessities. and the most important purposes of Islamic law for students.